Upon the flight of the queen - Jones, Howard A (Jones, Howard A. Ring-sworn trilogy., 2019)
"A fast-paced adventure combined with an engrossing mystery, all set in a unique and original fantasy world. I can't wait to find out what happens next!" -Martha Wells, Hugo Award-winning author. In this sequel to For the Killing of Kings, Howard Andrew Jones returns to the Nine Realms of the Dendressi in Upon the Flight of the Queen to continue this imaginative and fun epic fantasy trilogy. While the savage Naor clans prepare to march on the heart of the Five Realms, Rylin Corimel infiltrates the highest of the enemy ranks to learn their secrets and free hundreds of doomed prisoners. His ailing mentor Varama leads the Altenerai corps in a series of strikes to cripple the Naor. Kyrkenall, Elenai, and the kobalin Ortok ride for the storm-wracked shifting lands to rekindle the alliance with the winged lizards known as ko'aye, the only possible counter to the terrible Naor dragons. Meanwhile, the queen is delving further and deeper into the magic of the mysterious hearthstones, in a frantic attempt to save the realms that just might doom them all. Praised for his ability to write modern epic fantasy that engrosses and entertains, Howard Andrew Jones delivers a sequel that expands the amazing world, relationships, and adventure that he introduced in the first book of this series"--